Busca de um perfil de biomarcadores para a Doença de Alzheimer : enfoque em genes da via inflamatória - Santos, Lígia Ramos dos (2017)
Alzheimer disease (AD) is a progressive neurodegenerative disease and the most common type of dementia that affects elders. As pathological features, it presents neurofibrillary tangles and amyloid plaques in the brain. In 98% of the cases, AD is sporadic or late-onset AD (LOAD) and the ɛ4 allele of APOE gene acts as the most risk factor. As the pathological events may appear years before the first symptoms of AD, the research seek to use biomarkers in AD pre-clinic phase to identify traces of the disease before it establishment. Therefore, the work aimed investigate the creation of a possible genetic biomarkers profile for Late-onset Alzheimer disease with the polymorphisms at the genes ABCA7 (rs3764650), MS4A6A (rs610932), CD33 (rs3865444), CR1 (rs6656401), BIN1 (rs744373), IL-6 (rs1800795), CLU (rs1136000) and APOE (rs429358 and rs7412) in a sample of patients and controls in Grande Vitória-ES population. The study performed was an association study with 241 individuals not consanguineous, including 159 individuals without Dementia matched by sex and age and 82 patients with diagnosis of probable AD. It was performed as genotyping Polymerase Chain Reaction – Restriction Fragment Length Polymorphism, Real-Time Polymerase Chain Reaction and sequencing of genotype standards. As statistic analysis, it was performed Chi-square test, Odds ratio, Confidential interval of 95%, Mann-Whitney and Logistic regression at SPSS software. It was consider p significance with value < 0.05. It was analyzed statistic epistasis in pares of polymorphisms from the same pathway to AD by Logistic regression. It was also calculated the Hardy-Weinberg Equilibrium for each group. It was found association only for rs3865444 CD33. This polymorphism had showed association to LOAD with GT genotype as protection factor (95% CI: 0.299-0.942; p=0.042). This result supports a role of protection of CD33 gene at inflammatory pathway to LOAD, since the CD33 protein may contribute with Aβ42 clearence in AD. The logistic regression analysis did not found association for the others polymorphisms when associated with others variables as age, gender, school level, ethnical background and APOE status. In epistasis analysis, it was found risk association among polymorphisms at APOE with BIN1 and APOE with CLU for LOAD. Theses results supports a role of APOE, BIN1 and CLU genes at metabolism, trafficking and endocytosis of lipid pathway in AD. Also, this data support the hypothesis that APOE and CLU genes may regulate together the elimination of Aβ formed in brain. Additionally, the result of interaction of BIN1 and APOE support the notion that BIN1 protein could participate in Aβ clearance by the internalization of Aβapoe complex. The results of the study gave an opening for a creation of a genetic biomarkers profile for LOAD in Grande Vitória-ES population.